2006
DOI: 10.1111/j.1464-410x.2006.06450.x
|View full text |Cite
|
Sign up to set email alerts
|

One week of ciprofloxacin before percutaneous nephrolithotomy significantly reduces upper tract infection and urosepsis: a prospective controlled study

Abstract: Urosepsis after percutaneous nephrolithotomy (PCNL) is a severe complication, and its avoidance can sometimes be difficult despite antibiotic prophylaxis. Authors from the UK with a considerable experience in this procedure describe a prospective controlled study using ciprofloxacin for 1 week before PCNL, and found that it significantly reduces the risk of urosepsis. OBJECTIVE To evaluate whether 1 week of ciprofloxacin before percutaneous nephrolithotomy (PCNL) in patients with stones of ≥ 20 mm or pelvicaly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
93
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 153 publications
(101 citation statements)
references
References 15 publications
4
93
3
Order By: Relevance
“…Number of tracts, blood transfusion, stone size and presence of pyelocaliectasis were identified as risk factors for the development of SIRS. Another study by Mariappan et al investigated 52 patients with stones ≥ 2cm and dilated pelvicalyceal systems to whom 1 week per os ciprofloxacin treatment was given as an extended antibiotic prophylaxis [12]. They found a 7% SIRS rate in these patients compared to 18% SIRS in the control group.…”
Section: Discussionmentioning
confidence: 99%
“…Number of tracts, blood transfusion, stone size and presence of pyelocaliectasis were identified as risk factors for the development of SIRS. Another study by Mariappan et al investigated 52 patients with stones ≥ 2cm and dilated pelvicalyceal systems to whom 1 week per os ciprofloxacin treatment was given as an extended antibiotic prophylaxis [12]. They found a 7% SIRS rate in these patients compared to 18% SIRS in the control group.…”
Section: Discussionmentioning
confidence: 99%
“…15 However, other investigators described supine position approach with different techniques including the use of flexible ureterorenoscope, with comparable About prophylactic antibiotics, all our patients received a full course antibiotics in case of proved growth in urine culture, and during induction of anesthesia as most of the protocols, however, Mariappan et al in their study showed that one week oral ciprofloxacin in case of large renal stone more that 20mm or in case of hydronephrosis significantly reduced the risk of urosepsis after PCNL procedures. 17 Fluoroscopy was done to monitor the access to the collecting system in all our steps of dilatation . Nephrostomy catheter was inserted by size 20F chest tube drainage catheter at the end of our procedure, the aim is to tamponade venous bleeding, to prevent urine extravasations or allow healing of minimal pelvicalyceal system injury and allow an access for a second look PCNL through the same tract in case of significant residual stones.…”
Section: Discussionmentioning
confidence: 99%
“…A prospective controlled study of patients undergoing percutaneous nephrolithotomy (Mariappan, Smith et al 2006) reported significant reduction in the risk of upper tract infection and urosepsis following 1 week of prophylactic ciprofloxacin. However this may not be extrapolated in cases of percutaneous nephrostomy not related to underlying calculus or nephrolithotomy, as the presence of calculus is known to be associated with increased risk of infection.…”
Section: Patient Preparationsmentioning
confidence: 99%
“…Several factors have been found to contribute towards increased risk of sepsis, and this includes the duration of the procedure itself, urine bacterial load, severity of urinary tract obstruction as well as presence of bacteria within the calculus (Mariappan, Smith et al 2006). Mariappan also reported higher risk of upper urinary tract infections in patients with calculi larger than 20mm or a dilated pelvicalyceal system.…”
Section: Sepsismentioning
confidence: 99%
See 1 more Smart Citation